Sistem Pakar Penentuan Plafon Kredit Konsumer pada PT. BDI - Des Suryani (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2011)
PT. BDI is one of the major banks in Indonesia. With the current economic situation, that bank provide product to help the Indonesian society especially for private employees / BUMN and entrepreneurs by providing venture capital loan or other uses are commonly referred to ready-borrow funds (dp sip), so that these products are widely used by the community. Giving this ceiling will vary in number depending on the assessment criteria component from each of borrowers. usability expert system is to accelerate the process of determining the ceiling loan of the borrowers. For search method is using Forward Chaining Method. This method uses the facts of the components provided by the debtor to obtain the conclusion of the ceiling amount received. conclusions of this expert system is able to provide information in the form of a ceiling amount to be received by the debtor to quickly and accurately based on the assessment component of the proposed Key word: expert system, loan consumer, forward chaining